PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MODEL INKUIRI TERBIMBING UNTUK MELATIHKAN KEMAMPUAN MULTI REPRESENTASI SISWA SMA - Binar Kurnia Prahani; Soegimin W.W; Leny Yuanita (Universitas Negeri Surabaya, 2017)
The purpose of this research is produce physics learning material through guided inquiry model that valid, practical, and effective to try multiple representation ability of student in senior high school. The development of learning material used the Kemp model and was tested in class X of SMAN 19 Surabaya second semester in academic year 2013/2014 with One-Group Pretest-Posttest Design. The data collection used observation method, test, and quetionnaires. The data analysis techniques used descriptive analysis of quantitative, qualitative and statistic non parametric. The results of this research are: 1) Learning material developed has a valid category; 2) Learning material in terms of a practical category in feasibility of lesson plans and the students activities in accordance with steps of guided inquiry model; and 3) The learning material effectiveness in terms of: (a) Improving students learning achievement seen from the n-gain score with high category; (b) Improving multiple representation ability of student by getting the n-gain score with high category and the analysis results of statistic non parametric are: 1) nothing different of multiple representation ability of student at each class, 2) different of multiple representation ability of student, and 3) nothing different of improving multiple representation ability of student at each class; and (c) The students responds toward material and implementation of learning are very positive. Its conclusion that the learning material through guided inquiry model are valid, practical, and effective to try multiple representation ability of student in senior high school Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran fisika model inkuiri terbimbing yang valid, praktis, dan efektif untuk melatihkan kemampuan multi representasi siswa SMA. Pengembangan perangkat pembelajaran menggunakan model Kemp dan diujicobakan di kelas X SMAN 19 Surabaya semester genap tahun ajaran 2013/2014 dengan One-Group Pretest-Posttest Design. Pengumpulan data menggunakan metode observasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif, kualitatif dan uji statistik non parametrik. Hasil penelitian ini menunjukkan,: 1) Perangkat pembelajaran yang dikembangkan berkategori valid; 2) Perangkat pembelajaran ditinjau dari keterlaksanaan RPP berkategori praktis dan aktivitas siswa sesuai dengan tahap-tahap pada model inkuiri terbimbing; dan 3) Keefektifan perangkat pembelajaran ditinjau dari: (a) Peningkatan hasil belajar siswa terlihat dari n-gain dengan kategori tinggi; (b) Peningkatan penguasaan kemampuan multi representasi siswa terlihat dari n-gain dengan kategori tinggi dan hasil analisis uji statistik non parametrik, yaitu: 1) tidak terdapat perbedaan kemampuan multi representasi awal siswa pada kelas yang satu dengan kelas yang lain, 2) terdapat peningkatan kemampuan multi representasi siswa, dan 3) tidak terdapat perbedaan peningkatan kemampuan multi representasi siswa pada kelas yang satu dengan kelas yang lain; dan (c) Respon siswa terhadap perangkat dan pelaksanaan pembelajaran sangat positif. Disimpulkan bahwa perangkat pembelajaran model inkuiri terbimbing yang dikembangkan valid, praktis, dan efektif untuk melatihkan kemampuan multi representasi siswa SMA.